The truce of al-Hudaybiyyah refers by the Qur’an as an ‘open victory’: An Analysis - Ab Halim, Asyiqin (Online Journal of Research in Islamic Studies, 2018)
The truce of al-Hudaybiyyah occurred in 6 AH / 628 AC was referred by the Qur’an as an ‘open victory’. Stated in surah al-Fath, the first and second verses describes the condition of the truce as “Verily We granted thee a manifest victory. That God may forgive thee thy fault of the past and those to follow: fulfill His favour of thee: and guide thee on the straightway’”[1] Although these verses and the whole surah was revealed after the treaty of al-Hudaybiyyah, initially they had not been interpreted by the Muslims as an ‘open victory’ since they were potrayed as the weaken side from the agreement. However, the sequences of the events occurred later had led to the victory of the Muslims. Muslims had gradually achieved a victory to another and eventually capable to conquer Makkah in 8 AH/630 AC. Thus, this article attempts to discuss the sequences of these events on how it led to the manifest or open victory to Muslims as mentioned in the Qur’an in surah An-Nasr, verse 1-3. [1] Surah Al-Fath (48): 1-2